การศึกษาความเป็นไปได้ในการลงทุนธุรกิจรถยนต์มือสองในอำเภอเมืองลำปาง - จาตุรนต์ อิทธิประภากุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of independent study is to examine the feasibility on an investment in used car business in Amphoe Mueang Lampang. This feasibility study mainly focuses on 4 aspects, namely marketing, technical, management and financial aspects. This study collects primary data from interview 4 used car business entrepreneurs who have been established the business in amphoe Mueang Lampang. The data are also collected by handling out questionnaires to 200 customers who have plan to buy used car within 2556 BE. In addition, secondary data are collected from journal, internet, books, magazines and related researchs. The results from this study will be consider whether to invest in used car business under the assumptions of the financial analysis factors, for instances Net Present Value, Internal Rate of Return, Profitability Index and Payback Period. This study covers more details in risk aspects of the project both in sensitivity analysis and scenario analysis in order to understand risks of the business from variety of parameters. According to the market analysis, the results show that the top 3 most important external factors customers concern about in buying used car are gasoline price, economic and family income/expenditure. The top 3 most important marketing mix factors are price, product and people. The management analysis reveals that this project should be operated as a corporation. The organization structure consists of one general manager, two salespersons, two vehicle inspector and one administrator. The project also hires three outsource positions as two security guards and one housekeeper. The results of the financial study show that the initial investment is 9,833,704 Baht. 5,380,204 Baht from owner and 4,453,500 Baht from bank loan. Under 5 years assumption period, the project breakeven point is to sell 6 used cars each month. The project financial analysis results show that Net Present value equals to 2,423,554 Baht and the Internal Rate of Return of project is 23.86% which is higher than the cost of capital. The project payback period is about 3 years and the profitability index is 1.26. However, project risk analysis results found that the rate of cost of the used car per unit affects Net Present Value more than the used car sales growth rate. Therefore, the investor should pay more attention to this factor in running used car business. In conclusion, used car business is feasible to invest in Amphoe Muang Lampang.